Флорокомплекс штучно намитих пісків у заплаві р. Десни: формування і сучасний стан - Лукаш, О.В. (Інститут ботаніки ім. М.Г. Холодного НАН України, 2008)
Флористический комплекс на искусственно намытых песках в пойме р. Десны на начальных этапах формируется за счет ксероморфных апофитов и адвентивных видов. Со временем во флорокомплексе возрастает роль автохтонных элементов. Трансформация песчаного намыва в карьер привела к уменьшению роли ксероморфных и возрастанию — гигроморфных аборигенных видов.
Полная трансформация болотного экотопа в пойме Десны сперва в песчаный намыв, потом— в карьер, что измененило гидрологический и солевой режимы, привело к появлению в спонтанной флоре региона новых видов (Ceratocarpus arenarius, Lactuca tatarica, Grindelia squarrosa,Hippophaё rhamnoides, Typha laxmannii), формированию благоприятных местопроизрастаний для малораспространённых видов слабозасолённых экотопов (Salsola tragus, Taraxacum bessarabicum, Bolboschoenus maritimus, Scirpus tabernamontani, Triglochin palustre, Rumex maritimus, R. ucrainucus, R. thyrsiflorus) и способствовало интенсивному распространению на локальной территории Hippophaё rhamnoides и Typha laxmannii. Formation of the floristic complex on artificial deposits of sands in floodplains of the Desna River in the initial stages is formed mainly by xeromorphic apophytes and alien plants. In due course the role of autochthonous elements in floristic complex grows. The transformation of artificially deposited sands into a sand-pit has caused reduction of xeromorphic species and increase of the role of hygromorphic species.
The complete transformation of the marsh ecotope in floodplains of the Desna River into artificially deposited sands and the sand-pit, which has caused changes of hydrological and salt modes, has resulted in occurrence in the spontaneous flora of the region of new species (Ceratocarpus arenarius, Lactuca tatarica, Grindelia squarrosa, Hippopha¸ rhamnoides, Typha laxmannii), has created favorable conditions for sporadically occurring species of faintly saline ecotopes (Salsola tragus, Taraxacum bessarabicum, Bolboschoenus maritimus, Scirpus tabernaemontani, Triglochin palustre, Rumex maritimus, R. ucrainucus, R. thyrsiflorus), also promoted intensive distribution in the local territory of Hippopha rhamnoides and Typha laxmannii.